2009
DOI: 10.1186/1476-072x-8-35
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical evaluation of integrated marsh management impact on mosquito vectors using before-after-control-impact (BACI) design

Abstract: BackgroundIn many parts of the world, salt marshes play a key ecological role as the interface between the marine and the terrestrial environments. Salt marshes are also exceedingly important for public health as larval habitat for mosquitoes that are vectors of disease and significant biting pests. Although grid ditching and pesticides have been effective in salt marsh mosquito control, marsh degradation and other environmental considerations compel a different approach. Targeted habitat modification and biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…On both marshes, larval densities declined in manipulated marshes relative to control marshes, resulting in a percentage of control of larval mosquito production in excess of 90% for at least 2 yr after the manipulations. Similar Þndings were reported for a recent study on Long Island, NY, where OMWM-type manipulations decreased the frequency of larval mosquito production by 70% on a treatment marsh compared with a control marsh (Rochlin et al 2009). The effects of the interventions on the proportion of sample stations that were wet and on the proportion of sample stations with larvae were present shed light on the mechanisms of these two approaches to marsh management.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…On both marshes, larval densities declined in manipulated marshes relative to control marshes, resulting in a percentage of control of larval mosquito production in excess of 90% for at least 2 yr after the manipulations. Similar Þndings were reported for a recent study on Long Island, NY, where OMWM-type manipulations decreased the frequency of larval mosquito production by 70% on a treatment marsh compared with a control marsh (Rochlin et al 2009). The effects of the interventions on the proportion of sample stations that were wet and on the proportion of sample stations with larvae were present shed light on the mechanisms of these two approaches to marsh management.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, these manipulations decreased the need for larvicide applications at these marshes. Rochlin et al (2009) also observed a decreased need for larvicide applications after OMWM-type alterations on their treatment marsh. An additional note that is worth mentioning is that another treatment site at Parker River NWR (site A), which had undergone ditch plugging in 1994 to control mosquito production, also exceeded larvicide threshold criteria on isolated sampling dates during this study (James-Pirri et al 2008).…”
Section: Discussionmentioning
confidence: 85%
“…Nixon (1982) judged that ditching was of "questionable value" for mosquito control. Recent studies of ditch modifications compared the treatments with control ditched marshes; the ditched marshes produced measurable numbers of mosquitoes (Rochlin et al 2009;James-Pirri et al 2009;Leisnham and Sandoval-Mohapatra 2011;Rochlin et al 2012), which of course suggests the ditches are not that effective at mosquito control.…”
Section: Invertebratesmentioning
confidence: 99%
“…Although not feasible at the federally designated Wilderness Area, another restoration scenario might be to fill the linear ditches, while also creating meandering tidal creeks and marsh pools, providing essential nekton habitat. This was recently done at a nearby salt marsh at Great South Bay, NY (Rochlin et al 2009). Often, historic tidal channels that had been lost in response to grid ditching (Adamowicz & Roman 2005) can be relocated and restored.…”
Section: Management Perspectivementioning
confidence: 99%
“…Some restoration efforts are underway or are being considered to remove ditches from the marsh landscape by filling, plugging at the mouth to encourage natural filling, or other techniques (e.g. Adamowicz et al 2004, Baustian & Turner 2006, Rochlin et al 2009). Also Open Marsh Water Management (OMWM), an alternative method to grid-ditching, is now widely implemented for mosquito control and has been offered as a technique to restore hydrology of grid-ditched marshes (Meredith et al 1985, Meredith & Lesser 2007.…”
Section: Introductionmentioning
confidence: 99%